Blood of my blood - Lyga, Barry (Lyga, Barry. I hunt killers trilogy, 2014)
Jazz Dent, who has been shot and left to die in New York City, his girlfriend, Connie, who is in the clutches of Jazz's serial killer father, Billy, and his best friend, Howie, who is bleeding to death on the floor of Jazz's own home in tiny Lobo's Nod, must all rise above the horrors their lives have become and find a way to come together in pursuit of Billy.